Pentoxifylline modulates activation of human neutrophils by amphotericin B in vitro. - Sullivan, G W (1992)
The antifungal agent amphotericin B (AmB) alters neutrophil (polymorphonuclear leukocyte [PMN]) function, and this may be the mechanism for some of the adverse effects caused by AmB. AmB is a potent inhibitor of PMN migration, increases PMN adherence and aggregation, and primes PMN for increased oxidative activity in response to a second stimulus. AmB also stimulates mononuclear leukocytes (MNLs) to release inflammatory mediators which augment the effects of AmB on PMN function. In the present study, we observed that the methylxanthine derivative pentoxifylline decreased the effects of AmB on PMN function. AmB (2 micrograms/ml) priming doubled PMN chemiluminescence stimulated by fMet-Leu-Phe. In the presence of MNLs, AmB priming increased fMet-Leu-Phe-stimulated PMN chemiluminescence to 622% of unprimed PMN activity. Pentoxifylline (100 microM) blunted the rise in AmB-augmented PMN chemiluminescence in the presence of MNLs to 282% of unprimed PMN activity, and pentoxifylline metabolites were active at 10 microM. Pentoxifylline (100 microM) also blocked AmB-augmented PMN oxidative activity in whole blood, as measured by nitroblue tetrazolium reduction. In the presence of MNL, AmB (2 micrograms/ml) doubled the expression of the important PMN adherence factor Mac-1. Pentoxifylline (1 mM) decreased AmB-stimulated PMN Mac-1 expression back to unstimulated amounts. In the presence of MNLs, AmB (2 micrograms/ml) decreased PMN nondirected and directed migration to fMet-Leu-Phe to 40 and 38% of control PMN migration, respectively. Pentoxifylline (300 microM) counteracted AmB inhibition of nondirected and directed migration to fMet-Leu-Phe, resulting in migration that was 71 and 87% of control PMN migration, respectively. In contrast, the methylxanthine caffeine (100 muM) increased AmB-enhanced chemiluminescence but did not affect AmB-inhibited PMN migration. Pentoxifylline should be evaluated as adjunctive therapy to lessen the inflammatory damage caused by AmB.